Penampilan Hasil Gabah dan Karakter Agronomi Padi Hibrida di Bantul, Yogyakarta - Bambang Sutaryo; Cicilia Tri Kusumastuti (Savana Cendana, 2018)
Research of Performance of yield and agronomic components for hybrid rice in Bantul, Yogyakarta. for five hybrid rice varieties namely Hipa 8, Hipa 9, Hipa Jatim 2, Hipa 18 and Hipa 19 was conducted at Sonopakis, Bantul, Yogyakarta during the dry season (DS) of 2015. Seedling of 15 days with one seedling per hill was planted using Jajar Legowo 4:1 system, with a plant spacing of 25 x 12,5 x 50 cm. Plot size per variety was 2000 m2. Ciherang and IR64 as a popular variety planted using the same population by farmers were used as checks. Data were analyzed using t-test. Hipa 8 and Hipa 19 gave the highest yield (7.9 and 7.5 t/ha, respectively) compared with check varieties and the other varieties tested. The highest yield on Hipa 8 and Hipa 19 were contributed by the highest of the main components, namely the number of filled grains, total grain number, and the panicle number. All varieties showed early to moderate maturity, except Hipa 9 and Hipa Jatim 2 of 120 and 123 days, respectively.